Pengaruh Prosedur Pendataan Barang Terhadap Efektifitas Pengelolaan Data Aset Inventaris Di CV. Yummys Motherlacto Indonesia - Ach Baihaqi Annas Firmansyah; Ayundha Evanthi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
CV. Yummys Motherlacto Indonesia faces challenges in the management process of inventory assets, particularly focusing on inventory asset data procedures. The challenges include procedures for registering new assets and manually recording assets using Microsoft Excel and physical logbooks. The objective of this research is to find solutions to address these challenges, aimed at enhancing the efficiency and effectiveness of the process. In this study, the researchers utilized knowledge in inventory management to handle inventory asset management, employing Enterprise Asset Management (EAM) as a solution to transition from manual methods to greater efficiency by developing an application using appsheet. Additionally, they leveraged forecasting techniques such as Demand Forecasting and extrapolation techniques, alongside ABC Analysis for categorizing the value of inventory assets. By overcoming the aforementioned challenges through solutions derived from the mentioned theories and knowledge, the research yielded outcomes that effectively improved the efficiency of the asset management process.